2012
DOI: 10.1038/ismej.2012.69
|View full text |Cite
|
Sign up to set email alerts
|

Acyl-homoserine lactone-dependent eavesdropping promotes competition in a laboratory co-culture model

Abstract: Many Proteobacteria use acyl-homoserine lactone (AHL)-mediated quorum sensing to activate the production of antibiotics at high cell density. Extracellular factors like antibiotics can be considered public goods shared by individuals within a group. Quorum-sensing control of antibiotic production may be important for protecting a niche or competing for limited resources in mixed bacterial communities. To begin to investigate the role of quorum sensing in interspecies competition, we developed a dual-species co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
117
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(131 citation statements)
references
References 49 publications
12
117
2
Order By: Relevance
“…MalR might be a degenerate AHL quorum-sensing signal receptor. There is increasing evidence that AHL receptors play an important role in interspecies competition (30,31). Antibiotics and cytotoxic factors are often activated by AHL quorum sensing (31)(32)(33), and as discussed above, MalR (11) and QscR (29) are antibiotic activated.…”
Section: Discussionmentioning
confidence: 99%
“…MalR might be a degenerate AHL quorum-sensing signal receptor. There is increasing evidence that AHL receptors play an important role in interspecies competition (30,31). Antibiotics and cytotoxic factors are often activated by AHL quorum sensing (31)(32)(33), and as discussed above, MalR (11) and QscR (29) are antibiotic activated.…”
Section: Discussionmentioning
confidence: 99%
“…Chandler et al demonstrated this fact recently in a coculture model using the soil saprophytes Burkholderia thailandensis and Chromobacterium violaceum (145). Bruns et al demonstrated that signaling compounds were able to trigger microbial growth (146).…”
Section: Signaling Compoundsmentioning
confidence: 98%
“…These extracellular products are often important for nutrient acquisition, interspecies competition, or virulence (6)(7)(8). In Pseudomonas aeruginosa, QS control of secreted proteases provides fitness benefits, because the proteases are produced only when they can be used efficiently (9).…”
mentioning
confidence: 99%